Implementasi Pembelajaran Sentra Dalam Meningkatkan Kecerdasan Siswa Di Tkit Al Mumtaz Jayanti Tangerang - Solihin, Solihin (LPPM STAI La Tansa Mashiro, 2024)
The purpose of this study is to explore and analyse the implementation of centre learning in Al Mumtaz Integrated Islamic Kindergarten (TKIT) Jayanti, Tangerang, which focuses on improving various aspects of children's intelligence, including cognitive, motor, social, emotional, and spiritual intelligence. At TKIT Al Mumtaz, centre learning is implemented through various types of centres, such as preparation centres, macro role centres, child role centres, faith and piety centres, block centres, cooking centres, and body exercise centres. Each centre is designed to develop children's potential in a fun way and according to their stage of development. The results show that the implementation of centre learning has a significant impact in improving children's intelligence at TKIT Al Mumtaz Jayanti. Children who were actively involved in various centre activities showed improvements in cognitive skills, such as the ability to solve problems, communicate and think critically. They also show progress in social and emotional intelligence, including the ability to co-operate, empathise and manage their feelings. This approach also strengthens children's character development, which is crucial to forming individuals who are not only intelligent, but also well-rounded Keywords: center-based learning, children's intelligence.